Heidegger. The Co-Pertinence of Dasein and Being. A Confrontation with Kant - Segura Peraita, Carmen (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
In dialogue and confrontation with Kant, Heidegger discovers elements which allow him to deepen in his understanding of the co-pertinence of Dasein and being. This is a non-transcendental understanding, which arises in the midst of the unending debate with Kant’s transcendental philosophy. Heidegger considered that a transformation had come about in metaphysics of the ὑποκείμενον-οὐσία into the «apophantic subject». This should have reached its culmination with Kant, but in discussion with Kant, Heidegger changed the course, allowing a redefinition of the relationship between subject and object, identifying thinking with being, thus definitively reaffirming his thesis by which being and Dasein are co-pertinent